The Application of the Doctrines of Severability and Competence- Competence in the UAE - ELBANA, MOHIEELDIN MOSAAD (2014)
Arbitration is considered one of the best options available to parties for resolving their disputes. Nowadays, courts strongly encourage arbitration, and thus, has been largely adopted locally and internationally. With that, this dissertation aims to determine whether, or not, the UAE arbitration practice in respect of the arbitral jurisdiction aligns with the international practice. In addition, this dissertation will also examine the importance and implications of Competence-Competence and severability doctrines under the UAE law. In-depth research has been done to answer these issues. This includes, without limitation, going through a series of reviews and gathering information from different sources such as journals, books, court judgments, awards, and articles. We discovered that there is an urgent need to introduce new global concepts within the effective legislation, including the competence-competence and severability concepts, to tackle the issue of who decides the jurisdiction of the tribunal and make sure that the arbitration agreement is not ineffective. This finding suggests that, in the UAE, these principles need to be applied in all cases except when there is a solid challenge to the basis of the arbitration such as when there are valid allegations that the party did not agree on the arbitration agreement. Therefore, we recommend forming an independent body, which can be in the form of a judicial committee (be it an independent circuit in local courts or linked with the technical office of the Minister of Justice or the Chairman of the court (the “Committee”)) to deal with the issues that negatively affect the continuation of the arbitral proceedings on summary basis. The role of this Committee shall be to facilitate the determination of cases and to support the parties’ autonomy. If the Committee finds a major reason that prevents the arbitral proceedings, as if the arbitration agreement was never formed or the dispute is not arbitrable, the case shall forthwith be referred to the competent court for determination, otherwise the matter shall be referred to the tribunal to continue the arbitral proceedings.